Glioblastoma Multiforme in a Patient with Isolated Hemimegalencephaly - Chrastina, Jan; Novak, Zdenek; Brazdil, Milan; Hermanova, Marketa (Journal of Neurological Surgery Reports, 2015)
We present an exceptional case of a patient with hemimegalencephaly and secondary intractable epilepsy treated with vagus nerve stimulation (VNS) and subsequent glioblastoma development in the hemimegalencephalic hemisphere 6 years after surgery. VNS (at age 18 years) led to a 60% reduction of intractable seizures. However, symptoms of intracranial hypertension suddenly occurred 6 years after surgery. A computed tomography scan revealed a brain tumor in the hemimegalencephalic hemisphere. Pathologic examination confirmed glioblastoma multiforme. The genetic background of hemimegalencephaly is discussed here, with attention paid to the available data about the malignant transformation of malformations of cortical development (MCDs). The case points to the need for adequate clinical and radiologic follow-up care for patients with MCDs including hemimegalencephaly.
Keywords: malformations of cortical development; hemimegalencephaly; epilepsy; glioblastoma multiforme